Smart Water Irrigation for Rice Farming through the Internet of Things - Binayao, Regie Porras; Mantua, Paul Vincent Lagapa; Namocatcat, Holy Rose May Pardillo; Seroy, Jade Kachel Klient Bocboc; Sudaria, Phoebe Ruth Alithea Bacotot; Gumonan, Kenn Migan Vincent Casicas; Orozco, Shiela Mae Malbas (International Journal of Computing Sciences Research; Vol 8 (2024): Volume 8, 2024)
Purpose – This study intends to build smart water irrigation for rice farming using IoT and micro-controller devices with solar panel support. The system demonstrates the capabilities of automated irrigation by reducing physical labor through smart monitoring of the temperature, soil moisture, and humidity using multiple sensors. Method – This paper uses an agile methodology as it is suitable for reiterative operation for the development of the prototype. Results - The mean result for the interpretation of data gathered for the system’s adaptability and flexibility is 4.32. This figure shows that the selected farmers who took the survey understood and agreed with the prototype and its capability as an effective functionality to solve the problems in rice farming. Conclusion – The researchers were able to develop a smart water irrigation for rice farming using IoT and micro-controller devices with solar panel support and the respondents also agreed that the Smart water irrigation for rice farming using IoT and micro-controller devices with solar panel support is practical and valuable. Recommendations – Integration of a decision support system: A decision support system that can Analyze data collected from IoT sensors and provide further recommendations. Based on the results, it is also suggested that future researchers use drip irrigation, instead of flood irrigation. Research Implications – Smart water irrigation has the potential to revolutionize agriculture, enhance environmental sustainability, and address pressing global challenges related to water resources and food security. These implications highlight the importance of continued research and innovation in this field.